Graphitic carbon coupled poly(anthraquinone) for proton shuttle flow-in-a-cell application. Issue 12 (13th March 2017) - Mathi, Selvam; Kumar, Rudra; Nagarale, Rajaram K.; Sharma, Ashutosh
Abstract : An abstract showing the sandwich assembly of electro-osmotic pump along with graphitic carbon coupled polyanthraquinone and pump performance. Abstract : Coupled electron and proton transport are an integral part of non-gassing electro-osmotic pumps (EOP). The kinetics of the electrode limits the kinetics of the electron transfer and hence the flow. This is observed in the present study with newly synthesized graphitic carbon covalently coupled to poly(anthraquinone) (PAQ). When EOP with identical electrodes were assembled, proton shuttle maintained the reversible flow, which was linearly dependent on the k s values. A Laviron plot was used to calculate the electron-transfer rate constant k s and transfer coefficient α, and their linear dependency on content of graphitic carbon was observed. The best k s value obtained was 0.67 s −1 for 15PAQ. The sandwich-type flow-in-a-cell showed the best result of ∼40 μL min −1 cm −1 V −1 electro-osmotic flux for 15PAQ. It reveals that a balanced combination of graphitic carbon and PAQ is the prime requirement for high-performance electrode materials to be used in microfluidic devices and energy applications.